Price volatility effects on trading returns in agricultural commodity derivatives in South Africa - Motengwe, Chrisbanard Themba (My University, 2013)
Recent unexpected variability in the earnings of agribusinesses in South Africa has led stakeholders to ask as to why projected financial performance tended to be so different from the actual results achieved. This paper aims to make an empirical contribution to the discussion on the effects of soft commodity price volatility on the returns of entities whose major business involves derivatives trading in agricultural commodity products. Firstly, mathematical models for commodity price volatility are determined for the major agricultural commodities on the South African Futures Exchange (SAFEX) using the autoregressive conditional heteroskedasticity (ARCH) and the generalised autoregressive conditional heteroskedasticity (GARCH) type of approaches. Secondly, the study then seeks to ascertain whether there are causality links between the commodity price volatility and the returns or earnings realised by selected agribusinesses over time. The paper then discusses some trading strategies that are applicable given that commodity price volatility can be forecasted using the statistical models identified under the study.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: South African Futures Exchange; Agribusiness; Commodities; Price volatility